The Effects of Entrepreneurial Orientation and Sustainability Orientation Towards Sustainable Entrepreneurship of MSMEs in Jakarta with Entrepreneurial Bricolage as Mediation - Graciella Audrey Kurniawan; Frangky Selamat (Graduate Program of Universitas Tarumanagara, 2023)
This research is conducted to know the effects of entrepreneurial orientation and sustainability orientation towards sustainable entrepreneurship of MSMEs in Jakarta with entrepreneurial bricolage as mediation. This research used non-probability sampling through convenience sampling to obtain 119 respondents which are the people in MSMEs in Jakarta that are in the creative economy sector. Data are collected online through a questionnaire distributed through Google Forms. The data are processed with PLS-SEM method and SmartPLS 3.3.3 software. Result shows that entrepreneurial orientation and sustainability orientation influenced entrepreneurial bricolage of MSMEs in Jakarta positively and significantly, entrepreneurial bricolage influenced sustainable entrepreneurship of MSMEs in Jakarta positively and significantly, and entrepreneurial bricolage mediates both relationship of entrepreneurial orientation and sustainability orientation with sustainable entrepreneurship of MSMEs in Jakarta positively and significantly.